By any other name : a novel [compact disc, unabridged] - Picoult, Jodi, 1966- (Random House Audio, 2024)
In 1581, Emilia Bassano, like most young women of her day, is allowed no voice of her own. But as the Lord Chamberlain's mistress, she has access to all theater in England, and finds a way to bring her work to the stage secretly. And yet, creating some of the world's greatest dramatic masterpieces comes at great cost: by paying a man for the use of his name, she will write her own out of history. In the present, playwright Melina Green has just written a new work inspired by the life of her Elizabethan ancestor Emilia Bassano. Although the challenges are different four hundred years later, the playing field is still not level for women in theater. Would Melina, like Emilia, be willing to forfeit her credit as author, just for a chance to see her work performed? Told in intertwining narratives, this sweeping tale of ambition, courage, and desire asks what price each woman is willing to pay to see their work live on, even if it means they will be forgotten.